Control interno y su incidencia en la rotación del personal agrícola de la empresa reybanpac cl. Zona Vergel, año 2023 - Guaman Tello, Vanessa Erleny (2025)
The study titled "Internal Control and Its Impact on the Turnover of Agricultural Personnel at Reybanpac C.L., Zona Vergel, Year 2023" addresses the issue of high turnover among agricultural personnel, which affects the company's labor and operational stability. The objective is to evaluate internal control and its impact on staff turnover within the organization. The methodology employed includes field, descriptive, and documentary research, using inductive, deductive, and analytical methods through the application of the COSO model, worker surveys, and an interview with the manager. The results identified weaknesses in internal control, such as a rushed selection process, insufficient incentives, lack of training, and inefficient supervision, leading to the design of strategies aimed at